Ube2v1-mediated ubiquitination and degradation of Sirt1 promotes metastasis of colorectal cancer by epigenetically suppressing autophagy - Shen, Tong; Cai, Ling-Dong; Liu, Yu-Hong; Li, Shi; Gan, Wen-Juan; Li, Xiu-Ming; Wang, Jing-Ru; Guo, Peng-Da; Zhou, Qun; Lu, Xing-Xing; Sun, Li-Na; Li, Jian-Ming (Journal of hematology and oncology, 2018)
Ubiquitination is a basic post-translational modification for cellular homeostasis, and members of the conjugating enzyme (E2) family are the key components of the ubiquitin-proteasome system. However, the role of E2 family in colorectal cancer (CRC) is largely unknown. Our study aimed to investigate the role of Ube2v1, one of the ubiquitin-conjugating E2 enzyme variant proteins (Ube2v) but without the conserved cysteine residue required for the catalytic activity of E2s, in CRC. Immunohistochemistry and real-time RT-PCR were used to study the expressions of Ube2v1 at protein and mRNA levels in CRC, respectively. Western blotting and immunofluorescence, transmission electron microscopy, and in vivo rescue experiments were used to study the functional effects of Ube2v1 on autophagy and EMT program. Quantitative mass spectrometry, immunoprecipitation, ubiquitination assay, western blotting, and real-time RT-PCR were used to analyze the effects of Ube2v1 on histone H4 lysine 16 acetylation, interaction with Sirt1, ubiquitination of Sirt1, and autophagy-related gene expression. Ube2v1 was elevated in CRC samples, and its increased expression was correlated with poorer survival of CRC patients. Ube2v1 promoted migration and invasion of CRC cells in vitro and tumor growth and metastasis of CRC cells in vivo. Interestingly, Ube2v1suppressed autophagy program and promoted epithelial mesenchymal transition (EMT) and metastasis of CRC cells in an autophagy-dependent pattern in vitro and in vivo. Moreover, both rapamycin and trehalose attenuated the enhanced Ube2v1-mediated lung metastasis by inducing the autophagy pathway in an orthotropic mouse xenograft model of lung metastasis. Mechanistically, Ube2v1 promoted Ubc13-mediated ubiquitination and degradation of Sirt1 and inhibited histone H4 lysine 16 acetylation, and finally epigenetically suppressed autophagy gene expression in CRC. Our study functionally links Ube2v1, an E2 member in the ubiquitin-proteasome system, to autophagy program, thereby shedding light on developing Ube2v1 targeted therapy for CRC patients.